2008
DOI: 10.1108/13673270810859523
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge domains and knowledge conversion: an empirical investigation

Abstract: Purpose-The purpose of this paper is to present evidence of how different domains of knowledge (basic, experiential, emotional and innovative knowledge) relate to knowledge conversion processes (socialization, externalization, combination and internalization) in the firm. Design/methodology/approach-Confirmatory principal component analyses were performed on knowledge domain and knowledge conversion variables. Path analyses, based on stepwise multiple regressions, were performed in order to determine the stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 41 publications
1
16
0
2
Order By: Relevance
“…As shown, the SECI model has mainly been used in theory or for descriptive purposes and case studies; indeed, approximately half of the studies are theoretical articles (n = 55), whereas the remaining empirical studies include qualitative case studies (n = 20) and quantitative investigations (n = 33) with high empirical heterogeneity (Gourlay, 2006). Furthermore, only some empirical studies have tested the model's dimensionality, for instance showing that different knowledge processes are associated to specific domains of knowledge (Byosiere and Luethge, 2008) or are related to distinct outcomes (Alavi and Leidner, 2001;Chen and Chen, 2006). Some studies have also found that the effectiveness of a knowledge management process depends on the circumstances under which it was used; thus, individuals may employ different types of knowledge creation processes in order to better perform different types of tasks (Becerra-Fernandez and Sabherwal, 2001;Chou and He, 2004).…”
Section: Some Conceptual and Measurement Issuesmentioning
confidence: 99%
“…As shown, the SECI model has mainly been used in theory or for descriptive purposes and case studies; indeed, approximately half of the studies are theoretical articles (n = 55), whereas the remaining empirical studies include qualitative case studies (n = 20) and quantitative investigations (n = 33) with high empirical heterogeneity (Gourlay, 2006). Furthermore, only some empirical studies have tested the model's dimensionality, for instance showing that different knowledge processes are associated to specific domains of knowledge (Byosiere and Luethge, 2008) or are related to distinct outcomes (Alavi and Leidner, 2001;Chen and Chen, 2006). Some studies have also found that the effectiveness of a knowledge management process depends on the circumstances under which it was used; thus, individuals may employ different types of knowledge creation processes in order to better perform different types of tasks (Becerra-Fernandez and Sabherwal, 2001;Chou and He, 2004).…”
Section: Some Conceptual and Measurement Issuesmentioning
confidence: 99%
“…Experiential L&D also generated positive effects on performance and follows the same explanation offered for participative L&D, except that in this case, the human capital and dynamic capabilities will emerge from greater self‐awareness, whereas in terms of participative L&D, the source of human capital and dynamic capabilities will emanate from social interactions of executives. The positive effects of experiential L&D on organisational performance is corroborated by scholars positing that experience‐based knowledge plays an important role in the development of tacit knowledge, which in turn, drives innovative and competitive advantage (Byosiere & Luethge, ).…”
Section: Discussionmentioning
confidence: 88%
“…Yet, knowledge accumulation, knowledge sharing and knowledge conversion is a key resource of an organisations capacity to turn capabilities into competencies and skills that make a difference in practice (Eisenhardt and Martin, 2000;Byosiere and Luethge, 2008). It is one thing to capture and store knowledge (Bassi, 1999), but it is quite another to share it so that a teams' practical application is more evident.…”
Section: Knowledge Sharingmentioning
confidence: 97%
“…What is understood intuitively needs to be translated into a form that can be understood. While method-based learning is clearly invoked where one learns the knowledge to the point where it becomes second nature (Byosiere and Luethge, 2008), different behaviour through the use of metaphor, dialogues or analogies will be more useful for participation. In S-A teams where there is more freedom in thought and action and a stronger level of adaptability is required, it is reasonable to suggest that knowledge participation processes will be enhanced by more rather than less emergent learning.…”
Section: Knowledge Sharingmentioning
confidence: 98%